Research on Financial Regulation and Sustainable Development of Real Estate Markets: Taking Hangzhou City of Zhejiang Province as an Example - Ge, Jiayi (International Journal of Global Economics and Management, 2024)
The sustainable development of real estate is related to the interests of all parties, and it is of great significance to strengthen the macro-control and supervision of the real estate market to promote the sustainable development of the property market. This paper, taking Hangzhou as an example, points out that changes have occurred in Hangzhou's current macro-control policy system and the latest regulatory policies through literature review and case analysis. These changes are based on land supply, developer credit management, presale fund supervision, and financing credit support for enterprises, etc. These policies have played a positive role in the current sustainable development and transaction of Hangzhou's real estate. However, in the long run, there are still shortcomings in the top-level design of regulatory policies, policy implementation, and regulatory systems. This paper believes that in order to promote the sustainable and healthy development of Hangzhou's real estate market, improvements need to be made in policy optimization, regulatory models, and regulatory systems, so as to better play the unique role and value of policy regulation and better serve the overall economic situation. The research of this paper will also play a positive reference role for the real estate regulatory policies of other cities.